PENGARUH STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kurniansah, - (2019)
This research is a quantitative research that aims to determine the effect of Capital Structure and Investment Decisions on Profitability. The study was conducted on transportation sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique uses a purposive sampling method. The selection of samples from 34 transportation sub-sector companies listed on the Indonesia Stock Exchange from 2013 to 2017 period resulted in 9 companies that could be accepted. The type of data used is secondary data. Data collection techniques for the purposes of this study were carried out by literature and documentation techniques. Data tabulation was performed using the Microsoft Excel 2010 program. Data analysis and hypothesis testing in this study used the Multiple Panel Linear Regression Analysis with the SPSS 25 program and a 5% significance level. The results obtained from the testing in this study are (1) Capital Structure stated with Debt to Equity Ratio (DER) is not affected by profitability, (2) Investment Decisions stated with Fixed Assets Turnover have a positive significant effect on Profitability.